Forms of interaction in the project Medea - Petrova, Snezhina (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
Medea theatre project, one of the main focuses in the artistic programme of Plovdiv: 2019 European Capital of Culture, has developed different forms of interaction with participants and audiences. This is one of its main characteristics and the current report describes and analyses the specific approaches to attach to the creative process participants from outside â€“ children, organizations and audience: socio-dramatic and art workshops with children, clipclaptheatre: Campaign for the support of childrenâ€™s education in theatre in the social medias, â€žselfie pointâ€ at The TERRAIN MEDEA EXHIBITION and scenario for life interaction with theatre audience.